Prediction of the Number of Graduates Absorption by the Field of Expertise - Farida, Ida; Hariyadi, Guruh Taufan; Setiawan, Aries (Universitas Dian Nuswantoro Semarang, 2023)
The study program accreditation process also includes reporting forms filled in with the number of graduates working according to their field of expertise. A low conformity rate will indicate a lack of training and skills for graduates. If the conformity rate is high, it will affect the results of accreditation to increase and make the level of public trust in the study program higher, as well as from the perspective of graduate staff users. The study program needs to know the data of its graduates earlier as a step to increase the compatibility rate of the field of work with the field of lectures for its graduates. These problems can be minimized by carrying out a prediction process on the suitability of graduate fields. The variable used to predict is a data series of the number of graduates working in the right field over a certain period of time. The use of linear regression for predictions in the case of determining the exact field really helps make it easier for study programs to help predict the number of students who graduate by working in the right field. This study uses a linear regression method.